WORKSHOP PENULISAN KARYA ILMIAH ARTIKEL UNTUK MENINGKATKAN KOMPETENSI PROFESIONAL GURU - Sundahry, Sundahry; Irdes Putra, Yogi; Avana, Nurlev; Mufti, Dhini; Pratama, Putra (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
Workshop on writing scientific articles to improve teachers' professional competence at UPT SDN 03 Simpang. The aim of this activity is (1) to provide (sharing) training and assist elementary school teachers in writing scientific articles appropriately and (2) to increase insight and improve the skills of elementary school teachers in writing scientific articles and publishing them in scientific journals. This community service activity was carried out for UPT SDN 03 Simpang teachers. There were 12 participants in the activity. The methods used in this training activity are lectures and discussions, guidance and training, and consultation. Lecture and discussion methods convey information about scientific articles, theories about scientific articles, their benefits, and theories about writing them. Guidance and training methods are used to follow up to finalize the material presented in lectures and discussions. It is hoped that with direct practice, participants will be more skilled at writing scientific articles. The consultation method is used as a means of guidance in the field if they still experience difficulties in writing scientific articles. This training activity was carried out several times, which can provide input and benefits, including (1) elementary school teachers receive training and assistance in writing scientific articles and matters related to scientific articles, and (2) insight and skills elementary school teachers improved in writing scientific articles.